Proceedings of the 15th International Conference on Artificial Intelligence and Law 2015
DOI: 10.1145/2746090.2746092
|View full text |Cite
|
Sign up to set email alerts
|

A study of query reformulation for patent prior art search with partial patent applications

Abstract: Patents are used by legal entities to legally protect their inventions and represent a multi-billion dollar industry of licensing and litigation. In 2014, 326,033 patent applications were approved in the US alone -a number that has doubled in the past 15 years and which makes prior art search a daunting, but necessary task in the patent application process. In this work, we seek to investigate the efficacy of prior art search strategies from the perspective of the inventor who wishes to assess the patentabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In the implementation, each section of a patent such as title, abstract, claims, IPC and description is indexed in a separate field. However, when a query is processed, all indexed fields are targeted as this generally offers best retrieval performance [33]. The relevance assessment is provided for the topic set (queries) which are patents and have title, abstract, IPC, description, and claims sections.…”
Section: A Testing Collections and Pre-processingmentioning
confidence: 99%
“…In the implementation, each section of a patent such as title, abstract, claims, IPC and description is indexed in a separate field. However, when a query is processed, all indexed fields are targeted as this generally offers best retrieval performance [33]. The relevance assessment is provided for the topic set (queries) which are patents and have title, abstract, IPC, description, and claims sections.…”
Section: A Testing Collections and Pre-processingmentioning
confidence: 99%
“…While it is known that query length in operational interactive IR systems (in particular Web search engines) is rather short, typically between two and three terms long ( 31 , 32 ), in other IR contexts queries may be longer, ranging from ten to thousands of terms ( 33 , 34 ). Therefore, several researchers have investigated strategies for query length reduction, for the purpose of removing ambiguous and noisy terms.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the query is reduced by removing the least similar segments to the query. In ( 33 ), the authors proposed to study several query reduction techniques and their impact on the task of patent prior art search. They have shown that while query reduction techniques have a mitigated impact on mid-length queries, they are very effective on long queries such as an extended abstract or a description.…”
Section: Related Workmentioning
confidence: 99%
“…We developed a baseline IR system for patent prior art search on the top of the Lucene search engine and LM (Dirichlet smoothing, and Jelinek-Mercer smoothing) scoring functions based on [2]. We used Lucene to index the English subset of the CLEF-IP 2010 dataset 1 that contains 2.6 million patent documents and a subset of 1281 topics (queries) in the English test set where we determined at least one valid, relevant English document was available.…”
Section: Baseline Ir Frameworkmentioning
confidence: 99%
“…Kim et al [6] provided diverse query suggestion using aspect identification from a patent query to increase the chance of retrieving relevant documents. Magdy et al [9] and Bouadjenek et al [2] studied different query expansion and reduction techniques for patent search on CLEF-IP 2010, and reported little improvement with automatic methods. Magdy et al [10] further compare the best two systems in CLEF-IP 2010.…”
Section: Related Workmentioning
confidence: 99%